Memory in a global age : discourses, practices and trajectories - Assmann, Aleida 1947- Hrsg; Conrad, Sebastian 1966-; Internationales Forschungszentrum Kulturwissenschaften (Palgrave Macmillan memory studies, 2010)
Addressing painful memories : apologies as a new practice in international relations / Christoopher Daase -- Australian memory and the apology to the stolen generations of indigenous people / Danielle Celermajer and A. Dirk Moses -- The past in the present : memories of state violence in contemporary Latin America / Elizabeth Jelin --Vietnam, the new left and the Holocaust : how the Cold War changed the discourse on genocide / Berthold Molden -- The Holocaust : a global memory? Extensions and limits of a new memory community / Aleida Assmann -- Globalization, universalism, and the erosion of cultural memory / Jan Assmann -- Victimhood nationalism in contested memories : national mourning and global accountability / Jie-Hyun Lim -- Remembering Asia : history and memory in post-Cold War Japan / Sebastian Conrad -- Globalizing memory in a divided city : Bruce Lee in Mostar / Grace Bolton and Nerina Muzurovi#-- 'Fragments of reminiscence' : popular music as a carrier of global memory / Ana Sobral -- Neda : the career of a global icon / Aleida Assmann and Corina Assmann